Poles’ Motivations for Choosing Public Benefit Organizations (to Donate 1% of Income Tax) and Building Local Civic Community - Piechota, Grażyna (Journal of Public Governance, 2011)
For a few years Poles have had the possibility to transfer 1% of their income tax to various public benefit organisations. The liberalisation of regulations concerning the transfer, launched three years ago, introduced a competitive element between the organisations trying to obtain the taxpayers’ money. Thus public benefit organisations take up various promotional activities aimed at getting as much money as possible for performing their statutory tasks. The subject of this study is, however, not the actions undertaken by the organisations, but the motivation of Poles for choosing an organisation to which they transfer 1% of their income tax.